The effects of acute LPS-induced inflammation on cardiac morphology, geometry andfunction in spontaneously hypertensive rats - Fako, Kealeboga Mme (University of the Witwatersrand, Johannesburg, 2024)
It has been established that systemic inflammation negatively impacts myocardial structure and function, especially in individuals with comorbidities such as hypertension. Acute exposure to lipopolysaccharide (LPS), resulting in acute high-grade inflammation, has been demonstrated to induce cardiomyocyte oedema and apoptosis in the short-term, resulting in left ventricular (LV) systolic and diastolic dysfunction. While exposure to LPS-induced inflammation causes LV dysfunction in the short-term, the long-term consequences of exposure to acute high-grade inflammation on the structure and function of the heart remain unclear. Therefore, the current study aimed to ascertain the immediate and long-term effects of a single exposure to LPS on the structure and function of the heart and its potential compounding effects in a hypertensive model. Wistar-Kyoto rats (WKY, n=36) and spontaneously hypertensive rats (SHR, n=38) were randomly divided into two groups per rat strain. The control groups (WKY- control and SHR-control) received one injection of saline (1 ml/kg, i.p.). The LPS groups (WKY-LPS and SHR-LPS) received one injection of LPS (1 mg/kg, i.p.). Animals were then terminated either 24 hours (WKY, n=11; SHR, n=16) or 6 weeks (WKY, n=25; SHR, n=22) after the saline or LPS injections. Prior to termination, conventional and speckle-tracking echocardiography were performed on all animals under anaesthesia to ascertain the effects of LPS on LV geometry, systolic and diastolic function. Following termination, heart tissues were removed and weighed prior to storage. Total collagen content in the left ventricle was determined using the Picrosirius red stain. A mixed model two-way analysis of variance (ANOVA) was used to ascertain differences in echocardiographic parameters, the inflammatory cytokine and fibrosis, followed by a Tukey’s post hoc test. Pearson’s correlation was used to determine associations between collagen volume and echocardiographic parameters. After 24 hours, LPS administration significantly increased interleukin (IL)- 1β concentrations in WKY-LPS (p = 0.02), and SHR-LPS (p = 0.03) groups compared to their respective control groups. LPS-induced inflammation resulted in impaired LV diastolic function as indicated by impaired LV relaxation (E/A, septal and average e’) in SHR-LPS compared to SHR-control (all p < 0.05). LV passive stiffness (e’/a’) increased significantly in WKY-LPS compared to WKY-control (p = 0.05). However, heart weight was significantly higher in SHR-LPS compared to WKY-LPS due to hypertension, not inflammation (p = 0.02). LPS-induced inflammation also significantly decreased LV systolic function in the short-term, as indicated by a reduced left ventricular outflow tract (LVOT) velocity time integral (VTI, p = 0.0004) and LVOT peak velocity (Vmax, p = 0.008) in SHR-LPS compared to SHR-control. Hypertension significantly decreased left ventricular ejection fraction (LVEF, p = 0.02) and endocardial fractional shortening (FSend, p =0.03), which are markers of global systolic function, in SHR-LPS compared to WKY- LPS. LVOT VTI (p = 0.02) and Vmax (p = 0.03) were significantly lower in the SHR-LPS compared to WKY-LPS in response to hypertension. LPS administration significantly reduced circumferential (p = 0.03) and longitudinal strain (p = 0.02), which are markers of early systolic dysfunction, in SHR- LPS compared to SHR-control. Hypertension significantly reduced circumferential (p= 0.0004) and longitudinal strain (p = 0.01), in SHR-control compared to WKY-control, and in SHR-LPS compared to WKY-LPS (both p < 0.0001). There were also reductions in circumferential strain rate in SHR-control compared to WKY-control (p = 0.01), and in both circumferential (p < 0.0001) and longitudinal strain rate (p = 0.0005), in SHR- LPS compared to WKY-LPS. In the animals that were terminated 6 weeks after LPS exposure, there were no differences in IL- 1β (all p > 0.05). LPS-induced inflammation had no effect on any of the LV diastolic or systolic function parameters in any of the groups (all p > 0.05). However, heart weight (p = 0.03) and normalised heart weight (p = 0.02) were significantly higher in SHR-control compared to WKY-control due to hypertension. Similarly, heart weight (p = 0.02) and normalised heart weight (p = 0.0006) were significantly higher in SHR-LPS compared to WKY-LPS in response to the effect of hypertension. Hypertension significantly impaired LV relaxation (reduced septal e’) in SHR-control compared to WKY-control (p = 0.04) and in SHR-LPS compared to WKY- LPS (p = 0.04). LPS-induced inflammation had no significant effects on LVOT VTI and LVOT Vmax (all p > 0.05). Hypertension significantly reduced LVEF (p = 0.03) and FSend (p = 0.04) in SHR-control compared to WKY-control, as well as LVOT VTI in SHR-control compared to WKY-control (p = 0.04). LPS administration had no significant consequences on circumferential and longitudinal strain as well as circumferential and longitudinal strain rate (all p > 0.05). Hypertension significantly decreased circumferential (p = 0.005) and longitudinal strain (p < 0.0001) in SHR-control compared to WKY-control, and longitudinal strain in SHR-LPS compared to WKY-LPS (p = 0.002). There were also reductions in circumferential (p = 0.01) and longitudinal strain rate (p < 0.0001) in SHR-control compared to WKY-control, and in longitudinal strain rate in SHR-LPS compared to WKY-LPS (p = 0.002) due to hypertension. In the short-term groups, inflammation was significantly associated with impaired LV relaxation and passive stiffness, while collagen volume was significantly associated with impaired LV relaxation and myocardial deformation. In the long-term groups, inflammation was associated with impaired LV relaxation, passive stiffness, myocardial deformation and collagen volume, while collagen volume was significantly associated with impaired LV relaxation. In conclusion, acute LPS-induced high-grade inflammation resulted in impaired LV diastolic and systolic function after 24 hours. These changes were worsened in the animals predisposed to hypertension. Although majority of the LV systolic and diastolic function variables were reversed after six weeks, alterations in morphological and myocardial deformation were not reversed. Therefore, a single dose of LPS administration may impact structural remodelling and myocardial strain in rats predisposed to hypertension in the long-term
A dissertation submitted in fulfillment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Science, School of Physiology University of the Witwatersrand, Johannesburg, June 2024
Keywords: Heart failure with preserved ejection fraction; Hypertension; Sepsis; Inflammation; Lipopolysaccharide; Echocardiography; UCTD; SDG-3: Good health and well-being